Boost the large driving photovoltages for overall water splitting in direct Z-scheme heterojunctions by interfacial polarization. Issue 11 (28th April 2022) - Gao, Xu; Shen, Yanqing; Liu, Jiajia; Lv, Lingling; Zhou, Min; Zhou, Zhongxiang; Feng, Yuan Ping; Shen, Lei
Abstract : Using direct Z-scheme heterojunction photocatalysts has been regarded as one of the most effective methods to separate photogenerated carriers for photocatalytic redox reactions of water splitting. Abstract : Using direct Z-scheme heterojunction photocatalysts has been regarded as one of the most effective methods to separate photogenerated carriers for photocatalytic redox reactions of water splitting. However, their unique band alignment results in small driving photovoltages, significantly limiting the overall photocatalytic efficiency. In this work, we propose two practical methods to address this problem in Z-scheme heterojunction photocatalysts. One is to introduce a large interfacial polarization. The other is to take wide-bandgap components. Nonpolar wide-bandgap PtO2 and GeC are chosen in this work, because these two nonpolar materials have a large difference in the work function to fulfil the requirement of their large interfacial polarization. Besides, it is convenient to make an effective comparison between our work and the previous works on the direct Z-scheme heterojunctions based on MoSe2 and WSe2 . Therefore, PtO2 /MoSe2 and PtO2 /WSe2 are also investigated in this work. Therefore, the material realization of such rational design is achieved and demonstrated in three van der Waals (vdW) two-dimensional (2D) polar heterojunctions: PtO2 /MoSe2, PtO2 /WSe2, and PtO2 /GeC. Our first-principles calculations show that the polar heterojunctions have an extended light absorption range (covering the near-infrared spectrum), small exciton binding energy, small global band gap, and large interfacial electric field, indicating a high efficiency of light utilization and carrier separation. The most important feature is their large driving photovoltages, up to 4 V for the oxidation evolution reaction (OER) and 2 V for the hydrogen evolution reaction (HER), induced by the large interfacial polarization and wide band gaps of 2D monolayer materials. The calculated Gibbs free energies demonstrate that such high photovoltages can smoothly drive both the OER and HER, implying a high redox efficiency for the proposed Z-scheme polar heterojunctions. Our work provides a significant strategy for designing the direct Z-scheme heterojunctions with high photocatalytic performance.